Consumer preference on the use of the Ford SYNC system: a netnographic study - Barreto, Iury Assis; Filho, Emilío José Montero Arruda (Revista de Administração da UFSM, 2019)
The decision to purchase a car is strongly symbolic and related to unique marketing approaches. Therefore, it is important to understand this phenomenon, particularly from the perspective of technological innovation. This article presents an analysis of the consumer’s preference in the segment of automobiles, emphasizing the preferences regarding the technological convergence with new multimedia systems, such as Ford SYNC. The study is based on a netnographic research that aims to understand how the variables hedonism, utilitarianism, social value, and self-extension influence the intention of buying a car, emphasizing the offer of embedded new multimedia systems, using the case of the Ford Motor Company’s SYNC system. The analysis revealed three categories, with implicit subcategories. The results demonstrate that the values discussed in theory directly influence the context and are preponderant in the consumers’ decision-making. This article contributes to the automobile industry by offering essential inputs regarding consumer preference, leading to reflections in the area of marketing to better understand future consumers’ demands.